Clinical Priority Setting and Decision-Making in Sweden: A Cross-sectional Survey Among Physicians - Catharina Drees; Barbro Krevers; Niklas Ekerstad; Annette Rogge; Christoph Borzikowsky; Stuart McLennan; Alena Buyx (Kerman University of Medical Sciences, 2022)
Background  Priority setting in healthcare that aims to achieve a fair and efficient allocation of limited resources is a worldwide challenge. Sweden has developed a sophisticated approach. Still, there is a need for a more detailed insight on how measures permeate clinical life. This study aimed to assess physicians' views regarding (1) impact of scarce resources on patient care, (2) clinical decision-making, and (3) the ethical platform and national guidelines for healthcare by the National Board of Health and Welfare (NBHW). Methods  An online cross-sectional questionnaire was sent to two groups in Sweden, 2016 and 2017. Group 1 represented 331 physicians from different departments at one University hospital and group 2 consisted of 923 members of the Society of Cardiology. Results  Overall, a 26% (328/1254) response rate was achieved, 49% in group 1 (162/331), 18% in group 2 (166/923). Scarcity of resources was perceived by 59% more often than 'at least once per month,' whilst 60% felt less than 'wellprepared' to address this issue. Guidelines in general had a lot of influence and 19% perceived them as limiting decisionmaking. 86% professed to be mostly independent in decision-making. 36% knew the ethical platform 'well' and 'very well' and 64% NBHW's national guidelines. 57% expressed a wish for further knowledge and training regarding the ethical platform and 51% for support in applying NBHW's national guidelines. Conclusion  There was a need for more support to deal with scarcity of resources and for increased knowledge about the ethical platform and NBHW's national guidelines. Independence in clinical decision-making was perceived as high and guidelines in general as important. Priority setting as one potential pathway to fair and transparent decision-making should be highlighted more in Swedish clinical settings, with special emphasis on the ethical platform.